2011
DOI: 10.1159/000323718
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Attenuates Neurodegenerative Changes in the NSC-34 Motor Neuron Cell Line Induced by Cerebrospinal Fluid of Sporadic Amyotrophic Lateral Sclerosis Patients

Abstract: Background: Motor neuron disease or amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the selective death of motor neurons in the spinal cord as well as motor cortex. Recently, vascular endothelial growth factor (VEGF) has been identified as a neurotrophic factor in animal models of familial ALS and other neurological diseases. Objective: The present study was designed to investigate the neuroprotective role of VEGF in the more prevalent sporadic form of ALS. Methods: We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…These patients were assessed for their functional status using the modified Norris scoring system and the ALS Functional Rating Scale (ALSFRS) [34]. The patients' mean age and disease duration matched well with our earlier studies [19,20]. A neurologist (A.N.)…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…These patients were assessed for their functional status using the modified Norris scoring system and the ALS Functional Rating Scale (ALSFRS) [34]. The patients' mean age and disease duration matched well with our earlier studies [19,20]. A neurologist (A.N.)…”
Section: Methodsmentioning
confidence: 94%
“…Kage et al [16] found its levels to decline in the spinal cord tissue of ALS patients, whereas Petri et al [17] showed that both FGF-2 and FGFR1 were preserved, even at the end stage of the disease. VEGF has recently emerged as a key neurotrophic factor for the growth, survival, and plasticity of motor neurons [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ALS/CSF only increases the cytosolic calcium concentration in motor neurons [24]. Furthermore, in NSC34, a hybrid cell line of neuroblastoma and motor neuron, ALS/CSF also exerts cytotoxic actions; however, this effect is only seen in differentiated cells [35,36]. Thus, it seems reasonable to conclude that the cytotoxic effect elicited by ALS/CSF on our MCN cultures is mostly exerted on cortical motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…the involvement of MAP kinases (Guo & Bhat, 2007), the interaction between bcl2-A1 and pro-caspase-3 (Iaccarino et al, 2011) or the involvement of kynurenine pathway implicated in the regulatory mechanisms of the immune response . In addition, different therapeutic agents have been tested in culture, such as the vascular endothelial growth factor (VEGF) (Kulshreshtha et al, 2011) or the semi-synthetic tetracycline called minocycline (Guo & Bhat, 2007), known for their neuroprotective effects in neurodegeneration models (Orsucci et al, 2009;Storkebaum et al, 2004). Similarly, other cell lines have been transfected with WT or mutant (G93A) hSOD1 and used for the same purpose: N18TG2 neuroblastoma, the non-neuronal Madin-Darby Canine Kidney (MDCK) (Raimondi et al, 2006) or the mouse embryonic fibroblast NIH3T3 cell lines (Shinder et al, 2001).…”
Section: Cell Line Culturementioning
confidence: 99%